Diseño geométrico y pavimento de la carretera Tabalosos – Pinto Recodo - Grández Vela, Gardel (2010)
This thesis was carried out with the application of technical concepts and noqnativos of the Design Manual for roads of low volume of traffic on roads with materials tread granular. Also the application of criteria acquired in the implementation of similar works, close to the area of the project. The design of a path meets a need justified socially and economically. Both concepts is correlate to establish them features technical and physical that should have the road that is projected, for them results sought are optimal, in benefit of the community that requires of the service, normally in situation of limitations very narrow of resources local and national. Taking into consideration as indicated in the previous paragraph, the present work is comprised all the study corresponding to the geometric design and pavement level affirmed of a path of low volume of traffic. Some of the parameters used in the said...